Biocultural approaches to developing well-being indicators in Solomon Islands - McCarter, Joe; Sterling, Eleanor J.; Jupiter, Stacy D.; Cullman, Georgina D.; Albert, Simon; Basi, Marlene; Betley, Erin; Boseto, David; Bulehite, Evan S.; Harron, Ryan; Holland, Piokera S.; Horning, Ned; et al. (Ecology and society, 2018)
To meet local and global aspirations toward sustainable resource management, we must first understand what success looks like. At global levels, well-being can be narrowly defined, which may clash with local values and cause adverse impacts. Melanesia is home to a complex mosaic of resource management systems, and finding locally appropriate indicators of success poses particular challenges. We propose that biocultural approaches can assist in developing grounded and appropriate well-being indicators. Biocultural approaches frame issues from the perspectives of place-based communities and work with resource users to develop desired outcomes. In doing so, biocultural approaches recognize links between people and the environment and seek to understand feedbacks between social and ecological components. Biocultural approaches may help to improve the fit between local aspirations and national or international actions and can also cocreate knowledge that draws on local knowledge and practice as well as western science. Here, we report on one such approach in Western Province, Solomon Islands, where rural communities are weighing a variety of trade-offs around the use of natural resources. The work encompasses four locations and seeks to define local needs and priorities, develop appropriate local indicators of success, assess indicator baselines, and catalyze appropriate action. Implementation challenges have included scaffolding between local and national levels and the diversity of the four locations. These have, however, been offset by the engaged nature of indicator creation, which assists communities in planning toward action around local definitions of wellbeing.